Propuesta de diseño arquitectónico de un mercado para el sector norte de la ciudad de Riobamba - Sancho Gaibor, David Alejandro (2016)
Riobamba is a city located in the central area of Ecuador and its main activities are trading and services. In recent years the development of the city, has caused that its territory extends, mostly to the north, creating a demand for equipment and other services which are not supplied because most of these services and equipment are nested in the central part of the city. This is the problem faced by distribution centers or marketplaces, which due to their characteristics and influence radius, cause an oversupply of these services in the city center, while in the north of the city the lack of these services or equipment is evident. For these reasons, the main purpose of this project is to provide a spatial solution, for the conduct of buying and selling activities be made in a marketplace that offers its customers, both sellers and buyers, the optimum conditions of comfort, safety, sanitation and equipment so they can do their activities properly. It should be kept in mind that the proposal places a modern type building, in which the design of commercial premises and all the spaces comply with all marketplaces, marketing centers and supply regulations, all according to the technical and demand traders’ criteria. The implementation of this service in the north of the city will reduce time in the activity of buying and selling products for the benefit of all citizens.